Hubungan Antara Film Animasi Anak dan Minat Belajar dengan Hasil Belajar Mata Pelajaran Pendidikan Agama Buddha Siswa Kelas III SD Maitreyawira Palembang - Venny Christiany; Yadi Sutikno; Hosan Hosan (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
This study aims to determine the relationship between the use of animated children's films and learning interest in Buddhist Religious Education among third-grade students at Maitreyawira Elementary School, Palembang. The background of this study is based on the need for engaging and motivating learning methods, particularly at the elementary school level. Animated films, as an audiovisual medium, are believed to stimulate student attention and engagement, while learning interest is an internal factor that influences learning outcomes. The research used a survey with a quantitative approach and correlation analysis techniques. The population in this study was all 132 third-grade students at Maitreyawira Elementary School, with a randomly selected sample of 57 students. The data collection instrument, a questionnaire that has been tested for validity and reliability, covered three main variables: animated films (X1), learning interest (X2), and learning outcomes (Y). Data normality was tested using the Kolmogorov-Smirnov test, while data analysis was conducted using simple correlation, partial correlation, and multiple correlation with a significance level of α = 0.05. The results of the study show that: (1) there is a significant relationship between children's animated films and student learning outcomes, (2) there is a significant relationship between learning interest and learning outcomes, and (3) there is a significant relationship between animated films and learning interest simultaneously towards learning outcomes. These findings conclude that the use of appropriate animated film media and increasing students' interest in learning can contribute positively to improving student learning outcomes, especially in the subject of Buddhist Religious Education.